O lugar-sertão: grafias e rasuras - Adriana Ferreira de Melo (2006)
A recurring term in the imaginary of Brazilian society, employed in Brazil since the Portuguese arrival, sertão (backland) remains present in the country ideary, assuming such extent of meanings and territorialities for over 500 years of Brazilian History, that refuses homogenizing conceptions and exact spatial delimitations. There are many sertões (backlands) framed, unframed and reframed, alongside History, from North to South of the country through various types of representation: discourses from the historiography, iconography, literature, oral narratives, music, film and even cartography. Such discourses constitute a rich material for the study of sertão and show clearly its polysemic and migrant spatial feature. From the profuse forest to the desert, from both the sense of uninhabited area and arid area, from cerrado to caatinga, sertão has named and still names distinct landscapings and spatialities, assuming an impressive diversity of images and meanings. A reflection about sertão as place, in contact with the representations enclosed in the novel Grande Sertão: Veredas (The Devil to Pay in the Backlands), attempting a transdisciplinar approach, contributes to the strengthing of the sociospatial studies and knowledge.